"It's less about you as a person and more about the result you can produce": examining coach and peer dynamics in sport from a psychosocial perspective. Issue 3 (4th May 2022) - Battaglia, Anthony; Kerr, Gretchen; Stirling, Ashley
ABSTRACT: Positive youth development (PYD) research in sport has often focused on the influence of coach and peer relations, yet the PYD research has been criticised for lacking sufficient theory. From a psychosocial development perspective, the nature and quality of interpersonal dynamics have a significant impact on the attainment of developmental outcomes for youth. In this research, we explored youth athletes' relational dynamics with coaches and peers in sport from a psychosocial perspective, framed by Erikson's theory of psychosocial development. Data were collected through semi-structured interviews with six youth athletes (three males and three females), 14–17 years of age. Thematic, structural, and performative narrative analysis procedures were used to examine youth's relational dynamics. Three overarching narratives were constructed from participant stories, including: unconditional relationships, conditional relationships, and seeking connections beyond sport. Youth athletes' stories are interpreted to suggest that often times the sport environment was not conducive to fostering positive coach-athlete and peer-peer dynamics, and hindered youth's psychosocial development. The youth athletes also revealed that when their interpersonal dynamics in sport were not perceived to fulfill their psychosocial needs, they shifted their focus to activities and environments outside of sport. The findings are discussed in relation to narratives and discourses in sport and developmental literature. Applications are drawn for supporting youth athletes' needs and continued sport participation through the facilitation of developmentally supportive relations in sport.